Synthesis of Six-Conductors Symmetrically Coupled Microstrip Line, Operating in a Normal Mode - Mikucionis, S.; Urbanavicius, V. (Elektronika ir Elektrotechnika, 2011)
Synthesis technique of six-conductor symmetrically coupled microstrip multiconductor line (MMCL), operating in a normal mode, is presented in this article. Results of the calculations acquired using the proposed mathematical model of an MMCL differ only by 3 % from the results acquired by other researchers. Examples of synthesis of six-conductor symmetrically coupled MMCL, operating in the even- and odd normal modes, are submitted in the article, also, dependences of parameters of these lines are investigated. It was established that the external conductors of an MMCL impart the most for ensuring the normal mode in an MMCL, and the organization of the internal conductors remains regular in this case. It is shown that parameters of the synthesized MMCL operating in the even normal mode depend in greater degree on the space between conductors, than MMCL operating in the odd normal mode. Ill. 7, bibl. 27, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.285